2019
DOI: 10.1055/a-0942-1756
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotorische und kognitive Entwicklung und Lebensqualität bei Kindern und Jugendlichen mit angeborenem Herzfehler

Abstract: ZusammenfassungKinder mit angeborenem Herzfehler (AHF) haben ein signifikantes Risiko für psychomotorische und kognitive Entwicklungsstörungen mit negativen Auswirkungen auf die psychosoziale Situation, akademische Leistung und Lebensqualität. Wichtigste Risikofaktoren sind angeborene Merkmale wie genetische Anomalien, Art und Schweregrad des AHF und sozioökonomische Faktoren. Pränatal können durch Hypoperfusion oder Hypoxie Reifungs- und Entwicklungsstörungen des Gehirns entstehen mit der Folge postnataler Lä… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Research has also shown that recurrent hypoxia and/ or hypercapnia can play a deleterious role in brain development, mainly in the first years of life, as previously reported in prematurity or congenital heart defects [6,19]. But relationships between neurocognition and severity of respiratory deficits have not been demonstrated in CCHS [30].…”
Section: Discussionmentioning
confidence: 95%
“…Research has also shown that recurrent hypoxia and/ or hypercapnia can play a deleterious role in brain development, mainly in the first years of life, as previously reported in prematurity or congenital heart defects [6,19]. But relationships between neurocognition and severity of respiratory deficits have not been demonstrated in CCHS [30].…”
Section: Discussionmentioning
confidence: 95%
“…The attention level assessment was performed using the first 9 items of the SNAP IV scale [29]. The SNAP IV scale is widely used [30][31][32] for screening attention deficit hyperactivity disorder in children; here, it was applied to parents and/or guardians in an appropriate room.…”
Section: Attention Deficitmentioning
confidence: 99%